2013
DOI: 10.1126/scitranslmed.3005681
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Fibrils Composed of Hexameric Peptides Attenuate Neuroinflammation

Abstract: Amyloid forming proteins Tau, alpha B crystallin, and amyloid P protein are all found in lesions of multiple sclerosis (MS). Our previous work established that amyloidogenic peptides from the small heat shock protein, alpha B crystallin(HspB5), and from amyloid β fibrils, characteristic of Alzheimer’s disease, were therapeutic in experimental autoimmune encephalomyelitis (EAE), reflecting aspects of the pathology of MS. To understand the molecular basis for the therapeutic effect, a set of amyloidogenic peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 53 publications
1
75
0
Order By: Relevance
“…amyloid fibrils | B-1a lymphocytes | experimental autoimmune encephalomyelitis | immune suppression | IL-10 A myloid fibrils, composed of hexapeptides, when injected into the peritoneum of mice stimulate an immune-suppressive response of sufficient magnitude to reduce the paralytic signs of experimental autoimmune encephalomyelitis (EAE) (1,2). Analysis of the differential gene-expression pattern in peripheral blood mononuclear cells revealed the amyloidogenic peptides (e.g., Tau 623-628) induced a type 1 interferon (IFN) response.…”
mentioning
confidence: 99%
“…amyloid fibrils | B-1a lymphocytes | experimental autoimmune encephalomyelitis | immune suppression | IL-10 A myloid fibrils, composed of hexapeptides, when injected into the peritoneum of mice stimulate an immune-suppressive response of sufficient magnitude to reduce the paralytic signs of experimental autoimmune encephalomyelitis (EAE) (1,2). Analysis of the differential gene-expression pattern in peripheral blood mononuclear cells revealed the amyloidogenic peptides (e.g., Tau 623-628) induced a type 1 interferon (IFN) response.…”
mentioning
confidence: 99%
“…In a 2013 article, we showed that hexapeptides that formed amyloid fibrils would suppress ongoing EAE. We showed that hexapeptides derived from β-amyloid, tau, prion protein, amylin and cryab all suppressed EAE (91).…”
Section: Translational Research At Stanford Over the Past 20 Yearsmentioning
confidence: 99%
“…The amyloid structures bind inflammatory mediators in plasma (89)(90)(91). Amyloid hexapeptide structures elicit a type 1 interferon response (93).…”
Section: Translational Research At Stanford Over the Past 20 Yearsmentioning
confidence: 99%
“…The hexapeptides bind a set of proinflammatory mediators in plasma, including acute-phase reactants and complement components. Administration of this amyloid-forming hexapeptide quickly lowers inflammatory cytokines in plasma such as IL-2 and IL-6, which are highly expressed in both acute and chronic MS lesions (31,41,86). The beneficial properties of amyloid-forming hexapeptides provide a potential new therapeutic direction.…”
Section: Nuclear Hormone Receptorsmentioning
confidence: 99%
“…Numerous phase 3 trials using these strategies have failed (90,91). Could amyloid molecules have a different role in MS (30,31)? Research on MS and its animal models point in this direction.…”
Section: Serpins and Other Inhibitory Proteinsmentioning
confidence: 99%